Ubiquitous Geometry: Measuring Authentic Surroundings to Support Geometry Learning of the Sixth-Grade Students. (March 2015) - Hwang, Wu-Yuin; Lin, Li-Kai; Ochirbat, Ankhtuya; Shih, Timothy K.; Kumara, W. G. C. W.
Ubiquitous geometry (UG) system that was designed and developed for the sixth-grade school students to learn geometry through measuring geometric objects surrounding them is presented. Real geometric objects could facilitate and consolidate students' geometric learning if students were given an opportunity to apply and practice geometric concept-related theories with their daily life objects. Therefore, the main purpose of this study was an attempt to improve students' interest and learning in geometry by providing the proposed UG system in tablet computers to measure daily life objects. Furthermore, two activities, namely, peer assessment and competition, were also designed to facilitate students' interaction and learning. Based on the results of one of the experiments, it is found that students' learning motivation and achievement have been improved significantly. Further, results of the pair t -test applied for pretest and posttest data show that students' geometry learning performances have been improved significantly by using the UG system. Regarding the involvement of students in the proposed activities, it was found that the amounts of competition records, reviewing own competition records, and the highest score of competition were significantly correlated with students' learning gains. The reasons behind were further investigated and found that it can help students to find their own mistakes and clarify misconceptions by doing and reviewing their own competition records. Therefore, it is clear that the proposed UG system and competition activities in this study can help the students to learn geometry better in comparison to traditional learning.